ANALYSIS OF INTERNAL CONTROL OVER THE PREPARATION OF FINANCIAL STATEMENTS IN UMKM BASED ON SAK EMKM (Study on Kopi Eksis) - Muhammad Reyhan; RM. Rum Hendramin; Reny Aziatul Pebriani (ProBisnis : Jurnal Manajemen, 2023)
This research is a qualitative research that aims to analyze internal control over the preparation of financial statements for MSMEs based on SAK MSME (Study Kopi Eksis). The data used in this study are primary data and secondary data. The method used in this research is descriptive qualitative analysis. The results of this study show that internal control in existing coffee there are several problems that hinder the recording of existing coffee and result in them not having compiled financial statements based on the applicable SAK MSME. Because there is no receipt for purchasing expenses or income to be recorded to compile financial statements from owners and employees. The conclusion of the results of this study is that business owners have not been able to implement the process of preparing financial statements based on SAK MSME.